The student engagement during the Covid-19 pandemic against remote teaching and the use of GoogleClassroom (Research, Society and Development, 2021)
The health crisis caused by Covid-19 boosted distance classes through remote learning and the use of platforms such as Google Classroom developed with a focus on integration between teachers and students. This article aimed to assess student engagement during the Covid-19 pandemic towards remote learning and the use of Google Classroom. This was a study of a basic nature, through bibliographical review, descriptive and exploratory, whose data were treated in a qualitative way to understand the participation of students in synchronous classes using the Google Classroom tool as a platform for monitoring the contents covered. in virtual classes during the pandemic. The research was carried out by conducting research in the CAPES and Google Scholar journals databases, using the following descriptors: “engagement”, “remote teaching”, “pandemic by Covid-19” and “Google Classroom”. After careful selection, 15 articles published in national journals between the years 2020 and 2021 were selected. The analysis of the articles demonstrates that the educational tools for online interaction allowed the realization of an innovative work, focused on the initial and continuing education of students, as well as in the integration among the participants of the class. The use of online platforms and virtual classes favored action planning, providing individual and collective knowledge gain.